The Features of Modern e-Marketing; Journal of Advanced Research in Law and Economics; Vol. 8, No. 8 - Safonova M. S. Marina Sergeevna; Ilyashchenko D. P. Dmitry Pavlovich; Kucherov A. V. Aleksey Vladimirovich; Ling V. V. Viktoriya Viktorovna; Smirnova Zh. V. Zhanna Venediktovna; Bukhtiyarova I. N. Irina Nikolaevna (2017, 2017)
Title screen